Class Wars : Money, Schools and Power in Modern Australia. - Taylor, Tony (Monash Studies in Australian Society Ser., 2018)
How Australians fund schooling has been a matter of bitter political, social and religious division for almost two hundred years. And it remains so. The 2012 Gonski Review, urging all jurisdictions to move towards consensus on a needs-based and socially just education system, has continued to encounter forms of political obstruction. By examining the principles, the motives and the means of those who, since Menzies, have fought to develop and maintain a class-based education system at the expense of a broader view of social justice, this book explains how and why Australian education policy remains mired in political controversy.